2022
DOI: 10.1038/s42003-022-03954-0
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting fertility from sperm motility landscapes

Abstract: Understanding the organisational principles of sperm motility has both evolutionary and applied impact. The emergence of computer aided systems in this field came with the promise of automated quantification and classification, potentially improving our understanding of the determinants of reproductive success. Yet, nowadays the relationship between sperm variability and fertility remains unclear. Here, we characterize pig sperm motility using t-SNE, an embedding method adequate to study behavioural variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In CASA systems, along with motility, speed (VCL, VSL and VAP) and linearity (LIN, STR and WOB) analyses can also be done objectively. It has been reported that motility, sperm velocity and linearity are associated with fertility, especially high values of VCL, VSL, VAP, LIN, STR, WOB and ALH have an important role in fertility success (Fernandez‐Lopez et al., 2022). C 60 HyFn supplementation has been suggested to prevent damages in motility, morphology, membrane functionality and viability in liquid‐stored (Özer Kaya et al., 2021) and frozen–thawed (Güngör et al., 2022) ram sperm by diminishing the imbalance in the oxidant–antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…In CASA systems, along with motility, speed (VCL, VSL and VAP) and linearity (LIN, STR and WOB) analyses can also be done objectively. It has been reported that motility, sperm velocity and linearity are associated with fertility, especially high values of VCL, VSL, VAP, LIN, STR, WOB and ALH have an important role in fertility success (Fernandez‐Lopez et al., 2022). C 60 HyFn supplementation has been suggested to prevent damages in motility, morphology, membrane functionality and viability in liquid‐stored (Özer Kaya et al., 2021) and frozen–thawed (Güngör et al., 2022) ram sperm by diminishing the imbalance in the oxidant–antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…(49,(50)(51)(52) Mass motility, in particular, is useful in ram semen motility assessment due to its correlation to in vivo sperm fertilizing capacity. (53) In addition, it has been shown that sperm motility is a convincing indicator of fertility in boar (54) and human. (55) Mitochondrial activity is related to sperm motility and has been associated to the ability of spermatozoa to fertilize oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the relationship between the degree of motility and the reproductive outcomes should also be emphasized. Sources of variability in sperm motility are found at different levels such as between sperm cells, ejaculates (from the same individual) and individuals [ 85 ]. It is also known that oxidative stress increases in samples with low sperm motility [ 86 ], and motility shows an inverse relationship with DNA fragmentation [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%